Enseignements universitaires francophones en milieux bi / plurilingues : légitimations et mises en œuvre - Danielle Omer; Frédéric Tupin (Recherches en didactique des langues et des cultures)
The thematic dossier of this issue stems from the work carried out by Éducation et Plurilinguismes: mises en perspective historiques et sociales a strand of the regional project Pluri-L1 (Pays de la Loire region), and is dedicated to diverse legitimations and implementations of Francophone university teaching in bi-plurilingual milieus. By taking into account the status of the languages involved, we would like to offer various perspectives on the development of a bi-plurilingual competence at the university be it from the point of view of the participants, the programmes put in place, or the challenges faced during their implementation. A varia section includes two studies that focus respectively on primary and secondary levels.